Instagram as a Promotional Media for the “Indah Bordir” Store - Renni Setyoningrum; Nur Maghfirah Aesthetika (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to describe how the use of the Instagram feature as a promotional medium is applied to a Indah Bordir shop in Sidoarjo. This research is based on an event that occurred and the fact that during the current COVID-19 pandemic, business actors experienced a very drastic decline in sales, this was due to the lack of visitors, the amount of competition, and the high cost of promotions incurred when using paid promotional media such as advertisements on television, print media or even on radio.This research method uses qualitative methods, data collection is obtained from observation and documentation. The results of this study indicate that, there are 12 features that are used as promotional media namely, Profile, Feed, Follow, Uploading Photos or Videos, Captions, Comments, Hashtags, Highlight Stories, Snapgrams, Live Broadcasts, Direct Messages, and Geotagging. While the other 5 are not used as promotional media namely, Home Page, Like, Explore, Story Archives, and Instagram Savepost.